Anatomical and histological comparative of the stomach and small intestines in rats and rabbits - Taghreed Hatem khamees; Hashim M. abdul-kareem (Al-Qadisiyah Journal of Pure Science, 2018)
The current study was conducted on 12 rabbit type Oryctolagus cuniculus eating herbs and 12 rat type Rattus norvegicus, which is one of the omnivores, which was in good health and regardless of their sex, as he used the 6 rabbits and the same number of rats for the purpose of anatomical study, which included measurement of height and weight of the stomach and small intestine in rabbits and rats, and use the 6 rabbits same number of rats for the purpose of histological study it took small samples of each part of the required parts and flooded formalin and conducted by the histological examination stages to know the structure of textile layers constituent and then measured the thickness of the four textile classes through eyepiece,this results showed the stomach in rabbits and rats are from the simple monogastric type, which are divided into nonglandular and glandular parts as the mucus layer of non glandular stomach lining with keratinized stratified squamous epithelium ,the stomach glandular are covered with simple columnar epithelium,consists submucosa of the connective tissue rich with blood vessels, nerves and muscle layer is composed of two layers of smooth muscles and the serosa layer.The histological structure of small intestine(the duodenum, jejunum and ileum) in rabbits and ratsis similar which consists of the mucous layer lining simple columnar epithelium stand it villi, which are long thin shape in rats and rounded paper form in rabbits The layer submucosa consists of connective tissue provider a lot of blood vessels and nerves, while the muscle layer it consists of two layers of smooth muscles, serosa layer represents the outer layer.